District Office Leadership Supporting Site-Level Teacher Collaborative Teams - Robert H. Voelkel; Christie W. Johnson; Fiaz Nadeem (MDPI AG, 2023)
Previous researchers examining professional learning communities (PLCs) claim that effective building-level PLCs improve teacher collaboration and student achievement. However, the role of district office leadership in supporting the success of site-level PLC teams is presently underexplored. Using an online survey, we investigated the claim that district office support enhances the success of site-level PLCs. Quantitative data were collected from 596 participants employed at 21 schools within 16 school districts in the north Texas region. Findings derived from correlation and structural equation modeling analyses revealed a significant direct effect of district office leadership support on successful PLC team implementation, suggesting that district leaders play an active role in the districtwide implementation of PLCs.